Method for green synthesis of nano-copper by using black rice extracting solution and application of nano-copper
By using the mixed reaction of black rice extract and CuSO4 solution, combined with precisely controlled process conditions, the problem of poor preparation quality of nano copper is solved, and the uniform particle size and efficient dispersion of nano copper are achieved, reducing the use of chemical raw materials and environmental pollution.
Patent Information
- Application Number
- CN202510251504.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-05
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-03-05
AI Technical Summary
The prior art does not consider the different concentrations of the solution, the influence of stirring rate and centrifugal rate on the dispersion of nanocopper in the reaction process, resulting in poor preparation quality of nanocopper.
The black rice extract is used as a green solvent and mixed with the CuSO4 solution. By controlling the heating extraction temperature, dilution treatment, stirring rate and centrifugal rate, the particle size distribution and dispersion of nano copper are accurately adjusted.
The preparation quality of nanocopper is improved, the uniformity of nanocopper particle size and efficient dispersion are ensured, and the use of chemical raw materials and environmental pollution are reduced.
Smart Images

Figure CN119733845A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal nano material preparation, and in particular to a method for green synthesis of nano copper by using black rice extract and its application. Background Art
[0002] Nanocopper is a new type of nanomaterial, specifically copper particles or copper nanocrystals with a diameter between 1 and 100 nanometers. It can be prepared by physical or chemical methods to produce different nanoparticle structures and properties, but the preparation process requires the use of toxic chemicals and preparations that are likely to pollute the environment. Therefore, replacing harmful ingredients with non-toxic, biocompatible and eco-friendly materials to synthesize metal nanocopper particles is an important research direction at present.
[0003] In addition, tetracycline pollutants in water bodies pose a serious threat to aquatic ecosystems, plants, aquatic organisms and human health. Nano-copper particles, due to their tiny size and high specific surface area, have a certain adsorption capacity for pollutants such as tetracycline.
[0004] Chinese patent publication number: CN102601381A, discloses a copper nanopowder and its preparation method. The powder is prepared by the following method: copper salt is prepared into a copper salt solution, and then a drag reducer and an inhibitor are added to obtain a copper salt mixed solution and preheat it; a reducing agent solution is prepared and its pH value is adjusted, and then preheated; the copper salt mixed solution and the reducing agent solution are mixed and stirred evenly, and the temperature is raised to the reaction temperature and reacted for a certain time to obtain a nano copper suspension solution; the nano copper suspension solution is subjected to aging treatment; the suspension solution obtained in the above step is vacuum filtered to obtain a copper nano powder without removing impurities; the copper nano powder is subjected to a certain treatment to obtain a copper nano powder wrapped in an organic solvent; the copper nano powder is vacuum filtered to obtain a wet copper nano powder; the copper nano powder obtained in the above step is subjected to low-temperature vacuum drying to obtain a finished copper nano powder.
[0005] It can be seen that the above technical solution does not take into account the effects of different solution concentrations, stirring rates during the reaction, and centrifugal rates on the dispersibility of nano-copper, resulting in poor preparation quality of nano-copper. Summary of the invention
[0006] To this end, the present invention provides a method and use for green synthesis of nano-copper using black rice extract, so as to overcome the problem that the prior art does not consider the influence of different concentrations of the solution and the stirring rate and centrifugal rate in the reaction process on the dispersibility of the nano-copper, thereby resulting in poor preparation quality of the nano-copper.
[0007] To achieve the above object, on the one hand, the present invention provides a method for green synthesis of nano-copper using black rice extract, comprising: Grinding black rice, mixing black rice powder with distilled water for heating extraction, cooling to room temperature and filtering under reduced pressure to obtain a black rice extract, and obtaining the absorbance of the black rice extract; When it is determined according to the absorbance that the preparation of the black rice extract does not meet the preset standard, increasing the temperature of the heating extraction; Add distilled water to a black rice extract that meets a preset standard for dilution, mix the diluted black rice extract with a CuSO4 solution for reaction, and stir at room temperature to obtain a nano copper solution, obtain a particle size standard deviation of the nano copper and an average particle size of the nano copper, and obtain a particle size uniformity characteristic value of the nano copper; When it is determined that the preparation of the nano-copper solution does not meet the preset standard according to the uniform characteristic value of the nano-copper particle size, a second determination is made according to the density of the nano-copper solution whether the preparation of the nano-copper solution meets the preset standard, or the stirring rate is increased; The nano copper solution that meets the preset standard is centrifuged, washed and vacuum dried to obtain nano copper, and the weight proportion of nano copper under the preset conditions is obtained. When it is determined that the preparation of nano copper does not meet the preset standard according to the weight proportion, the centrifugal speed of the centrifuge is reduced. The preset condition is to use an electronic balance to weigh the weight of nano copper with a particle size less than or equal to 6 nm.
[0008] Furthermore, the usage ratio of black rice powder to distilled water is 1.0 g to 5.0 g: 20 mL to 100 mL, the extraction time is 15 min to 30 min, and the heating extraction temperature is 80° C. to 100° C.
[0009] Furthermore, the molar concentration of the CuSO4 solution is 0.01 mol / L, the stirring time at room temperature is 5 min, and the stirring rate is 350 r / min.
[0010] Furthermore, the centrifugal speed of the centrifuge is 10000 rpm to 15000 rpm, and the centrifugal time is 9 to 15 minutes.
[0011] Further, the process of determining, according to the absorbance, that the preparation of the black rice extract does not meet the preset standard comprises: Compare the absorbance with the preset absorbance; If the absorbance is less than a preset absorbance, it is determined that the preparation of the black rice extract does not meet the preset standard, and the temperature of the heating extraction is increased according to the difference between the preset absorbance and the absorbance.
[0012] Further, the process of determining that the preparation of the nano-copper solution does not meet the preset standard according to the particle size uniformity characteristic value of the nano-copper includes: The particle size uniformity characteristic value is compared with a first preset particle size uniformity threshold and a second preset particle size uniformity threshold respectively; If the particle size uniformity characteristic value is greater than or equal to the first preset particle size uniformity threshold value and less than the second preset particle size uniformity threshold value, it is determined that the preparation of the nano copper solution does not meet the preset standard, and a second determination is made based on the density of the nano copper solution whether the preparation of the nano copper solution meets the preset standard; If the particle size uniformity characteristic value is greater than or equal to the second preset particle size uniformity threshold, it is determined that the preparation of the nano copper solution does not meet the preset standard, and the stirring rate is increased according to the difference between the particle size uniformity characteristic value and the second preset particle size uniformity threshold; The particle size uniformity characteristic value of nano-copper is determined by the particle size standard deviation and the average particle size of nano-copper.
[0013] Further, the density of the nano-copper solution is used to determine whether the preparation of the nano-copper solution meets the preset standard. If the density of the nano copper solution is less than the preset density, it is determined that the preparation of the nano copper solution meets the preset standard, and the nano copper solution meeting the preset standard is centrifuged; If the density of the nano copper solution is greater than or equal to the preset density, it is determined that the preparation of the nano copper solution does not meet the preset standard, and the amount of distilled water added to the black rice extract is increased according to the difference between the density of the nano copper solution and the preset density.
[0014] Further, the process of determining that the preparation of the nano-copper does not meet the preset standard according to the weight proportion of the nano-copper includes: If the weight proportion is greater than or equal to the preset weight proportion, it is determined that the preparation of the nano copper does not meet the preset standard, and the centrifugal speed of the centrifuge is reduced according to the difference between the weight proportion and the preset weight proportion.
[0015] There are several adjustment methods for reducing the centrifugal speed of the centrifuge, and each adjustment method has a different reduction range for the centrifugal speed.
[0016] On the other hand, the present invention also provides the use of nano-copper prepared by the method of green synthesis of nano-copper using black rice extract, wherein the nano-copper is used for adsorbing tetracycline in water.
[0017] Compared with the prior art, the invention has the beneficial effects that the invention adopts black rice and copper sulfate solution as raw materials, thereby reducing the use of chemical raw materials; the preparation quality of the black rice extract is tested by obtaining the absorbance of the black rice extract; the preparation effect of the nano-copper solution is tested by the particle size uniformity characteristic value of the nano-copper and the density of the nano-copper solution, and the preparation conditions are adjusted accordingly, thereby reducing the possibility of agglomeration of the nano-copper and improving the preparation efficiency; the preparation effect of the nano-copper is evaluated by the weight proportion of the nano-copper, thereby ensuring that the particle size distribution of the nano-copper meets the preparation requirements, and improving the preparation quality of the nano-copper.
[0018] Furthermore, the present invention adopts black rice as raw material, has relatively less process consumption and does not produce toxic by-products, is environmentally friendly and safe, belongs to a green synthesis process, and has a simple preparation method, realizes effective utilization of resources, reduces the use of chemical raw materials, and thus reduces pollution to the environment.
[0019] Furthermore, the present invention determines whether the preparation of the black rice extract meets the preset standard according to the absorbance, and increases the temperature of the heating extraction when it does not meet the preset standard, accurately controls the extraction conditions, ensures the quality of the black rice extract, and thus improves the preparation efficiency.
[0020] Furthermore, the present invention determines whether the preparation of the nano-copper solution meets the preset standard according to the uniform characteristic value of the nano-copper particle size, accurately evaluates the preparation effect of the nano-copper solution, intuitively reflects the dispersibility of the nano-copper particles, and improves the preparation quality of the nano-copper.
[0021] Furthermore, the present invention determines whether the preparation of the nano-copper solution meets the preset standard for a second time according to the density of the nano-copper solution, and more accurately evaluates the preparation quality of the nano-copper solution, thereby reducing the possibility of misjudgment.
[0022] Furthermore, the present invention determines whether the preparation of nano-copper meets the preset standard according to the weight proportion of nano-copper, and reduces the centrifugal speed of the centrifuge when it does not meet the preset standard, thereby improving the control of the particle size of nano-copper.
[0023] Furthermore, the present invention provides several adjustment methods for reducing the centrifugal speed of the centrifuge, and each adjustment method reduces the centrifugal speed of the centrifuge by a different amount, thereby achieving precise control of the reduction amount of the centrifugal speed of the centrifuge.
[0024] Furthermore, the green synthesized nano-copper of the present invention is applied to water purification. The nano-copper adsorbs tetracycline pollutants in the water and has a good adsorption effect on tetracycline, thereby providing new solutions and technical support for the field of water purification. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a flow chart of a method for green synthesis of nano-copper using black rice extract according to an embodiment of the present invention; Figure 2 A flow chart of determining whether the preparation of black rice extract meets preset standards according to an embodiment of the present invention; Figure 3 The UV-visible absorption spectrum of nano-copper synthesized greenly using black rice extract according to an embodiment of the present invention; Figure 4The high-resolution transmission electron microscopy image of nano-copper synthesized greenly using black rice extract in the embodiment of the present invention; A is a high-resolution transmission electron microscopy image of nano-copper at a scale of 2nm, B is a particle size distribution diagram of nano-copper particles, and C is a transmission electron microscopy image of nano-copper at a scale of 100nm; Figure 5 The infrared spectra of the nano copper and black rice extract obtained by the present invention are shown. DETAILED DESCRIPTION
[0026] In order to make the objects and advantages of the present invention more clearly understood, the present invention is further described below in conjunction with embodiments; it should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0027] The preferred embodiments of the present invention are described below with reference to the accompanying drawings. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present invention and are not intended to limit the protection scope of the present invention.
[0028] It should be pointed out that the data in this embodiment are obtained by comprehensive analysis and evaluation of the historical test data of the present invention three months before this test and the corresponding historical test results. It can be understood by those skilled in the art that the method of the present invention can determine the above parameters for a single item by selecting the value with the highest proportion as the preset standard parameter according to the data distribution, using weighted summation to use the obtained value as the preset standard parameter, substituting each historical data into a specific formula and using the value obtained by the formula as the preset standard parameter or other selection methods, as long as the method of the present invention can clearly define the different specific situations in the single determination process through the obtained values.
[0029] See also Figure 1 , Figure 2 , Figure 3 , Figure 4 as well as Figure 5 As shown, they are respectively a flow chart of a method for green synthesis of nano copper using black rice extract according to an embodiment of the present invention; a flow chart of determining whether the preparation of black rice extract meets a preset standard according to an embodiment of the present invention; an ultraviolet-visible absorption spectrum of nano copper green synthesized using black rice extract according to an embodiment of the present invention; a high-resolution transmission electron microscopy image of nano copper green synthesized using black rice extract according to an embodiment of the present invention; wherein A is a high-resolution transmission electron microscopy image of nano copper at a scale of 2 nm, B is a particle size distribution image of nano copper particles, and C is a transmission electron microscopy image of nano copper at a scale of 100 nm; and an infrared spectrum image of nano copper and black rice extract obtained according to the present invention.
[0030] On the one hand, an embodiment of the present invention provides a method for green synthesis of nano-copper using black rice extract, comprising: Step S1, grinding black rice, mixing black rice powder with distilled water for heating extraction, cooling to room temperature and filtering under reduced pressure to obtain a black rice extract, and obtaining the absorbance of the black rice extract; Step S2, when it is determined according to the absorbance that the preparation of the black rice extract does not meet the preset standard, increasing the temperature of the heating extraction; Step S3, adding distilled water to the black rice extract that meets the preset standard for dilution, mixing the diluted black rice extract with a CuSO4 solution for reaction, stirring at room temperature to obtain a nano copper solution, obtaining a particle size standard deviation of the nano copper and an average particle size of the nano copper, and obtaining a particle size uniformity characteristic value of the nano copper; Step S4, when it is determined that the preparation of the nano-copper solution does not meet the preset standard according to the particle size uniformity characteristic value of the nano-copper, a second determination is made according to the density of the nano-copper solution whether the preparation of the nano-copper solution meets the preset standard, or the stirring rate is increased; Step S5, centrifuging, washing and vacuum drying the nano-copper solution that meets the preset standard to obtain nano-copper, obtaining the weight proportion of nano-copper under the preset conditions, and reducing the centrifugal speed of the centrifuge when it is determined that the preparation of nano-copper does not meet the preset standard according to the weight proportion, The preset condition is to use an electronic balance to weigh the weight of nano copper with a particle size less than or equal to 6 nm.
[0031] Specifically, black rice powder was mixed with distilled water and heated to 85°C.
[0032] Specifically, the black rice is ground into powder using a grinder with a speed of 50 Hz to 70 Hz and a grinding time of 25 s to 40 s.
[0033] Specifically, the usage ratio of black rice powder to distilled water is 1.0g-5.0g:20mL-100mL, the extraction time is 15min-30min, and the heating extraction temperature is 80℃-100℃.
[0034] Specifically, the molar concentration of the CuSO4 solution is 0.01 mol / L, the stirring time at room temperature is 5 min, and the stirring rate is 350 r / min.
[0035] Specifically, in step S5, the centrifugal speed of the centrifuge is 10000 rpm to 15000 rpm, the centrifugal time is 9 to 15 min, and the vacuum drying is performed at 85 degrees Celsius for 24 hours; Specifically, the nano-copper solution that meets the preset standards is centrifuged, washed, and vacuum dried, and then nano-copper with a particle size less than or equal to 6 nm is obtained by an electronic balance.
[0036] Specifically, the process of determining that the preparation of the black rice extract does not meet the preset standard according to the absorbance includes: Compare the absorbance with the preset absorbance of 0.7; If the absorbance is less than a preset absorbance, it is determined that the preparation of the black rice extract does not meet the preset standard, and the temperature of the heating extraction is increased according to the difference between the preset absorbance and the absorbance.
[0037] Specifically, the absorbance of the black rice extract is obtained by an ultraviolet-visible spectrophotometer; the preset absorbance value is 0.7, and it can be understood that the preset absorbance value is obtained by taking the average value of the absorbance of the black rice extract at 495nm. In the historical detection data of this detection, there is a very obvious plasma resonance absorption peak at 542nm, and the peak shape is symmetrically distributed, indicating that a large amount of spherical nano-copper is generated in the solution, and the particle size is relatively uniform, but the preset absorbance value is not limited to this, and those skilled in the art can also adjust the value according to actual needs.
[0038] Specifically, the process of determining that the preparation of the nano-copper solution does not meet the preset standard according to the uniform particle size characteristic value of the nano-copper includes: The particle size uniformity characteristic value is compared with the first preset particle size uniformity threshold value of 1.03 and the second preset particle size uniformity threshold value of 1.21 respectively; If the particle size uniformity characteristic value is greater than or equal to the first preset particle size uniformity threshold value and less than the second preset particle size uniformity threshold value, it is determined that the preparation of the nano copper solution does not meet the preset standard, and a second determination is made based on the density of the nano copper solution whether the preparation of the nano copper solution meets the preset standard; If the particle size uniformity characteristic value is greater than or equal to the second preset particle size uniformity threshold, it is determined that the preparation of the nano copper solution does not meet the preset standard, and the stirring rate is increased according to the difference between the particle size uniformity characteristic value and the second preset particle size uniformity threshold; The average particle size and standard deviation of nano-copper are obtained by transmission electron microscopy and image analysis software such as ImagePro Plus; The particle size uniformity characteristic value of nano copper is obtained by the following formula:
[0039] In the formula, P represents the uniform characteristic value of the particle size of nano copper; D represents the average particle size of nano copper; D0 represents the preset average particle size of nano copper, and D0 is set to 9nm; α represents the weight of the average particle size of nano copper, and α is set to 0.45; σ represents the standard deviation of the particle size of nano copper; σ0 represents the preset standard deviation of the particle size of nano copper, and σ0 is set to 0.89; β represents the weight of the standard deviation of the particle size of nano copper, and β is set to 0.55.
[0040] In this embodiment, the first preset particle size uniformity threshold value is 1.03 and the second preset particle size uniformity threshold value is 1.21, which are obtained by comprehensive analysis and evaluation of historical detection data and corresponding historical detection results; The particle size uniformity characteristic value is an important indicator for evaluating the preparation quality of nano-copper solution, and can effectively control the uniformity of particle size distribution of nano-copper solution.
[0041] Specifically, the density of the nano-copper solution is used to determine whether the preparation of the nano-copper solution meets the preset standard. If the density of the nano copper solution is less than the preset density of 1.05 g / cm³, it is determined that the preparation of the nano copper solution meets the preset standard, and the nano copper solution meeting the preset standard is centrifuged; If the density of the nano copper solution is greater than or equal to the preset density, it is determined that the preparation of the nano copper solution does not meet the preset standard, and the amount of distilled water added to the black rice extract is increased according to the difference between the density of the nano copper solution and the preset density.
[0042] Specifically, the density of the nano-copper solution is obtained by a hydrometer; the preset density value is 1.05 g / cm³, but the preset absorbance value is not limited thereto, and those skilled in the art may also adjust the value according to actual needs.
[0043] A nanocopper solution with uniform density usually means that the particles are evenly distributed in the solution and the solution is stable. If the density fluctuates or is abnormal, it indicates that there are unstable phenomena such as particle agglomeration, precipitation or stratification in the solution.
[0044] Specifically, the process of determining whether the preparation of nano-copper does not meet the preset standard based on the weight proportion of nano-copper includes: If the weight ratio is greater than or equal to the preset weight ratio of 0.22, it is determined that the preparation of the nano copper does not meet the preset standard, and the centrifugal speed of the centrifuge is reduced according to the difference between the weight ratio and the preset weight ratio.
[0045] Specifically, the weight ratio is the ratio between the weight of nano-copper having a particle size less than or equal to 6 nm and the total weight of nano-copper; It is understandable that the centrifugal speed will directly affect the centrifugal force on the nano-copper particles during the centrifugal process. When the speed is too high, the nano-copper particles will be deformed or broken due to the excessive centrifugal force, thereby damaging the integrity of the nanostructure.
[0046] Specifically, there are several adjustment methods for reducing the centrifugal speed of the centrifuge, among which: If the weight ratio difference is less than the first preset weight ratio difference of 0.11, the centrifugal speed of the centrifuge is reduced to a corresponding value using the first adjustment coefficient of 0.99; If the weight ratio difference is greater than or equal to the first preset weight ratio difference and less than the second preset weight ratio difference of 0.21, the centrifugal speed of the centrifuge is reduced to the corresponding value using the second adjustment coefficient of 0.97; If the weight ratio difference is greater than or equal to the second preset weight ratio difference, the centrifugal speed of the centrifuge is reduced to a corresponding value using the third adjustment coefficient 0.95.
[0047] In another aspect, the present invention provides the use of nano-copper prepared by a method for green synthesis of nano-copper using black rice extract, wherein the nano-copper is used for adsorbing tetracycline in water.
[0048] Example 1
[0049] The black rice was ground with a 50 Hz grinder for 25 seconds to obtain black rice powder, 5 g of the black rice powder was mixed with 100 mL of distilled water, and the mixture was placed in a water bath heated to 80° C. and extracted for 20 minutes with continuous stirring during the extraction. After cooling to room temperature, the mixture was filtered under reduced pressure to obtain a black rice extract; Use ultraviolet-visible spectrophotometer to obtain the absorbance of black rice extract at 495nm wavelength, measuring absorbance is 0.8, greater than the preset absorbance 0.7, and it is judged that the preparation of black rice extract meets the preset standard; The black rice extract meeting the preset standard is added with distilled water and diluted to 250mL, the black rice extract after the dilution is mixed with the CuSO4 solution of 0.01mol / L of 250mL, and stirred for 5min at room temperature to obtain nano copper solution, and transmission electron microscope and Image Pro Plus are used to obtain the average particle diameter and particle size distribution standard deviation of nano copper, and the particle size uniform characteristic value obtaining nano copper is 0.83, which is less than the first preset particle size uniform threshold value 1.03, so it is judged that the preparation of nano copper solution meets the preset standard; The nanocopper solution that meets the preset standard is centrifuged at a speed of 10000 rpm for 10 min, the supernatant is removed, the precipitate is washed, and vacuum dried at 85°C for 24 h to obtain nanocopper. The weight of nanocopper with a particle size less than or equal to 6 nm and the total weight of nanocopper are weighed using an electronic balance, and the weight ratio of 0.20 is less than the preset weight ratio of 0.22, then it is determined that the preparation of nanocopper meets the preset standard.
[0050] Figure 3 This is the UV-visible absorption spectrum of nano-copper. The results show that a plasma resonance absorption peak appears at 542nm, and the peak is symmetrically distributed, indicating that a large amount of spherical nano-copper is generated in the solution, and the particle size is relatively uniform; the black rice water extract is used as a reducing agent to reduce the copper particles to nano-copper.
[0051] Figure 4This is a high-resolution transmission electron microscopy image of nano-copper. It can be seen that the nano-copper has good dispersion, is spherical, and has a small particle size. The average particle size is 9.03nm, and the nano-copper particle size that accounts for the largest proportion is between 6-8nm. The crystal plane spacing at the marked position of the nano-copper particles photographed by the high-resolution transmission electron microscope in the illustration was measured, and the distances were 2.05Å and 2.03Å respectively. By comparing with the standard PDF card of Cu, it was determined to be the 111 crystal plane of the Cu crystal structure.
[0052] Figure 5 The infrared spectra of nano copper and black rice water extract obtained by using black rice water extract as a reducing agent. In the infrared spectrum of black rice water extract, 3295cm -1 The stretching vibration of hydroxyl group is 2920cm -1 is the stretching vibration of methylene -CH2-, 1606cm -1 Related to the stretching vibration of carbon-carbon double bond, 1412 cm -1 The methyl group has an angle-variable vibration, 1049 cm -1 The peaks are the stretching vibration of the CO bond and the skeleton vibration of the CC single bond; these characteristic peaks confirm the presence of flavonoids and phenolic compounds in the black rice water extract, and the reducing property of these compounds enables the successful synthesis of nanocopper; the infrared spectrum of nanocopper has the same absorption peak as the black rice extract at similar wavenumbers, indicating that the surface of nanocopper is covered with certain components of the black rice water extract.
[0053] Application Example 1 Weigh 20 mg of the vacuum-dried nano-copper powder obtained in Example 1, add it to 50 mL of a 20 ppm tetracycline hydrochloride aqueous solution, and oscillate it in an oscillator at room temperature for 50 minutes; During the shaking process, samples were taken every 10 minutes, 2 mL each time, and the absorbance of tetracycline was measured at a wavelength of 365 nm using a spectrophotometer after centrifugation at 10,000 rpm for 5 minutes. The adsorption rate was calculated, and the maximum adsorption rate of 20 ppm tetracycline by the vacuum-dried nano-copper powder was 87%; This shows that nanocopper can effectively remove pollutants in water.
[0054] So far, the technical solutions of the present invention have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it is easy for those skilled in the art to understand that the protection scope of the present invention is obviously not limited to these specific embodiments. Without departing from the principle of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present invention.
[0055] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for green synthesis of nano copper using black rice extract, characterized in that: include: Grinding black rice, mixing black rice powder with distilled water for heating extraction, cooling to room temperature and filtering under reduced pressure to obtain a black rice extract, and obtaining the absorbance of the black rice extract; When it is determined according to the absorbance that the preparation of the black rice extract does not meet the preset standard, increasing the temperature of the heating extraction; Add distilled water to a black rice extract that meets a preset standard for dilution, mix the diluted black rice extract with a CuSO4 solution for reaction, and stir at room temperature to obtain a nano copper solution, obtain a particle size standard deviation of the nano copper and an average particle size of the nano copper, and obtain a particle size uniformity characteristic value of the nano copper; When it is determined that the preparation of the nano-copper solution does not meet the preset standard according to the uniform characteristic value of the nano-copper particle size, a second determination is made according to the density of the nano-copper solution whether the preparation of the nano-copper solution meets the preset standard, or the stirring rate is increased; The nano copper solution that meets the preset standard is centrifuged, washed and vacuum dried to obtain nano copper, and the weight proportion of nano copper under the preset conditions is obtained. When it is determined that the preparation of nano copper does not meet the preset standard according to the weight proportion, the centrifugal speed of the centrifuge is reduced. The preset condition is to use an electronic balance to weigh the weight of nano copper with a particle size less than or equal to 6 nm.
2. The method for green synthesis of nano-copper using black rice extract according to claim 1, characterized in that: The usage ratio of black rice powder to distilled water is 1.0 g to 5.0 g: 20 mL to 100 mL, the extraction time is 15 min to 30 min, and the heating extraction temperature is 80° C. to 100° C.
3. The method for green synthesis of nano-copper using black rice extract according to claim 1, characterized in that: The molar concentration of the CuSO4 solution is 0.01 mol / L, the stirring time at room temperature is 5 min, and the stirring rate is 350 r / min.
4. The method for green synthesis of nano-copper using black rice extract according to claim 1, characterized in that: The centrifugal speed of the centrifuge is 10000rpm~15000rpm, and the centrifugal time is 9~15min.
5. The method for green synthesis of nano-copper using black rice extract according to claim 4, characterized in that: The process of determining that the preparation of the black rice extract does not meet the preset standard according to the absorbance includes: Compare the absorbance with the preset absorbance; If the absorbance is less than a preset absorbance, it is determined that the preparation of the black rice extract does not meet the preset standard, and the temperature of the heating extraction is increased according to the difference between the preset absorbance and the absorbance.
6. The method for green synthesis of nano-copper using black rice extract according to claim 5, characterized in that: The process of determining whether the preparation of the nano-copper solution does not meet the preset standard according to the uniform characteristic value of the nano-copper particle size includes: The particle size uniformity characteristic value is compared with a first preset particle size uniformity threshold and a second preset particle size uniformity threshold respectively; If the particle size uniformity characteristic value is greater than or equal to the first preset particle size uniformity threshold value and less than the second preset particle size uniformity threshold value, it is determined that the preparation of the nano copper solution does not meet the preset standard, and a second determination is made based on the density of the nano copper solution whether the preparation of the nano copper solution meets the preset standard; If the particle size uniformity characteristic value is greater than or equal to the second preset particle size uniformity threshold, it is determined that the preparation of the nano copper solution does not meet the preset standard, and the stirring rate is increased according to the difference between the particle size uniformity characteristic value and the second preset particle size uniformity threshold; The particle size uniformity characteristic value of nano-copper is determined by the particle size standard deviation and the average particle size of nano-copper.
7. The method for green synthesis of nano-copper using black rice extract according to claim 6, characterized in that: The density of the nano-copper solution is used to determine whether the preparation of the nano-copper solution meets the preset standard. If the density of the nano copper solution is less than the preset density, it is determined that the preparation of the nano copper solution meets the preset standard, and the nano copper solution meeting the preset standard is centrifuged; If the density of the nano copper solution is greater than or equal to the preset density, it is determined that the preparation of the nano copper solution does not meet the preset standard, and the amount of distilled water added to the black rice extract is increased according to the difference between the density of the nano copper solution and the preset density.
8. The method for green synthesis of nano-copper using black rice extract according to claim 7, characterized in that: The process of determining, based on the weight proportion of the nano-copper, that the preparation of the nano-copper does not meet the preset standard comprises: If the weight proportion is greater than or equal to the preset weight proportion, it is determined that the preparation of the nano copper does not meet the preset standard, and the centrifugal speed of the centrifuge is reduced according to the difference between the weight proportion and the preset weight proportion.
9. The method for green synthesis of nano-copper using black rice extract according to claim 8, characterized in that: There are several adjustment methods for reducing the centrifugal speed of the centrifuge, and each adjustment method has a different reduction range for the centrifugal speed.
10. A use of nano copper prepared by the method for green synthesis of nano copper using black rice extract according to any one of claims 1 to 9, characterized in that: The nano copper is used for adsorbing tetracycline in water.
Citation Information
Patent Citations
Extraction method for black rice anthocyanins
CN105732742A
Method for achieving green synthesis on nano-silver through black rice pigment
CN110014166A
Method for preparing nano copper oxide particles by utilizing shrubalthea flower extracting solution, product and application
CN116395734A
Low-temperature preparation method and application of copper chrome black
CN118387925A
Method for preparing nano-copper particles from eucommia ulmoides extract and application of nano-copper particles in catalytic reduction reaction
CN119549733A
Cited By
Bimetal nanoparticle green synthesis method based on black rice extracting solution
CN120940656A